Genome analysis of poplar LRR-RLP gene clusters reveals RISP, a defense-related gene coding a candidate endogenous peptide elicitor - Petre, Benjamin; Hacquard, Stéphane; Duplessis, Sébastien; Rouhier, Nicolas (Frontiers in Plant Science, 2014)
In plants, cell-surface receptors control immunity and development through the recognition of extracellular ligands. Leucine-rich repeat receptor-like proteins (LRR-RLPs) constitute a large multigene family of cell-surface receptors. Although this family has been intensively studied, a limited number of ligands has been identified so far, mostly because methods used for their identification and characterisation are complex and fastidious. In this study, we combined genome and transcriptome analyses to describe the LRR-RLP gene family in the model tree poplar (Populus trichocarpa). In total, 82 LRR-RLP genes have been identified in P. trichocarpa genome, among which 66 are organised in clusters of up to seven members. In these clusters, LRR-RLP genes are interspersed by orphan, poplar-specific genes encoding small proteins of unknown function (SPUFs). In particular, the nine largest clusters of LRR-RLP genes (47 LRR-RLPs) include 71 SPUF genes that account for 59% of the non-LRR-RLP gene content within these clusters. Forty-four LRR-RLP and fifty-five SPUF genes are expressed in poplar leaves, mostly at low levels, except for members of some clusters that show higher and sometimes coordinated expression levels. Notably, wounding of poplar leaves strongly induced the expression of a defense SPUF gene named Rust-Induced Secreted protein (RISP) that has been previously reported as a marker of poplar defense responses. Interestingly, we show that the RISP-associated LRR-RLP gene is highly expressed in poplar leaves and slightly induced by wounding. Both gene promoters share a highly conserved region of approx. 300 nucleotides. This led us to hypothesize that the corresponding pair of proteins could be involved in poplar immunity, possibly as a ligand/receptor couple. In conclusion, we speculate that some poplar SPUFs, such as RISP, represent candidate endogenous peptide ligands of the associated LRR-RLPs and we discuss how to investigate further this hypothesis.